Effect of Application Frequency of the Entomopathogenic Fungus Hirsutellathompsonii (Fisher) on Damage Levels of Coconut Mite Aceriaguerreronis (Keifer) - Fernando, L. C. P.; Hapuarachchi, D. C. L.; Waidyarathne, K. P. (International Coconut Community Journal, 2011)
The effect of application interval of H. thompsonii (Fisher) on damage caused by the coconut mite, Aceriaguerreronis (Keifer) (Acari: Eriophyidae) in two coconut plantations in Sri Lanka was evaluated. In each plantation, coconut palms infested by coconut mite were treated with H. thompsonii isolate IMI 391722 at 2- and 3-monthly intervals and the fruits with H. thompsonii-infected coconut mite cadavers and percentage of harvested fruits in different damage categories were assessed. Infected coconut mite cadavers were found on up to 60% of the fruits treated with the fungus in both plantations at treatment frequencies. The effect of the treatments was site-specific. The treatments reduced the percentage of damaged-small size harvested fruits to half that of the untreated control in both plantations irrespective of the frequency of treatment. At one plantation, the percentages of undamaged fruits and fruits with discontinued damage were nearly doubled to that of untreated fruits.